Analysis of masseter and temporal muscles during surgical extraction of impacted third molars - Moraes, Michelle B. [UNESP]; Naclerio-Homem, Maria G.; Nascimento, Rodrigo D. [UNESP]; Amorim, Jose Benedito O.; Raldi, Fernando V. [UNESP] (My University, 2015)
With the aim of contributing to the discussion on stomatognathic system dysfunction after surgical procedures, this study compared the electromyographic activity of the superficial masseter and temporal masticatory muscles before, during, and after impacted mandibular third molar extractions. Muscular activity was recorded presurgery, transsurgery, immediately postoperatively, and on postoperative days 7, 15, and 30. Twenty patients requiring extraction of impacted mandibular third molars were selected and evaluated. In 20 patients who underwent mandibular third molar extractions, electromyography showed no alterations in muscle tone, and no statistically significant differences were observed in the left and right temporal and masseter muscles at any of the experimental periods at either mandibular rest or isometric contraction position. However, the degree of mouth opening increased 11.76% from pretreatment to 30 days after surgery. These results may reflect the shorter, careful extraction procedure performed by the surgeon.
Keywords: Electromyography; Masseter muscle; Masticatory muscles; Temporal muscle; Tooth avulsion; Tooth extraction